The influence of membranous stretched urethral length and urethral circumference on postoperative recovery of continence after radical prostatectomy: A pilot study - Cho, Dae Sung; Lee, Eun Ju; Kim, Se Joong; Kim, Sun Il (Canadian Urological Association Journal, 2015)
Introduction: We investigate the influence of stretched membranous urethral length (SUL) and urethral circumference (UC) on postoperative recovery of continence after radical prostatectomy (RP). Methods: To evaluate the distal continence zone intraoperatively, we individually measured and recorded stretched membranous urethral length (distance between the urogenital diaphragm and the prostate apex with cephalad retraction, SUL) and urethral circumference (UC) after exposure of the urethra. We analyzed the association between magnetic resonance imaging-measured membranous urethral length (MRIL) and urethral diameter (MRID) and intraoperative SUL and UC and influence on return to continence. Results: The mean patient age, SUL and UC were 66.5 ± 6.0 years, 24.2 ± 3.3 mm, and 27.5 ± 4.4 mm, respectively. MRIL and MRID were 11.3 ± 1.6 mm and 10.6 ± 1.9mm, respectively. In the bivariate correlation analysis, there was no statistically significant correlation between SUL and MRIL (p = 0.201) and between UC and MRID (p = 0.124). In the Kaplan-Meier curve analysis, cumulative continence rates between the two groups dichotomized at the median value according to age (p = 0.0519), SUL (p = 0.6583), UC (p = 0.4031), MRIL (p = 0.4042), and MRID (p = 0.8191) were not significantly different. High SUL-to-MRIL ratio (>2.2) was the only significant predictor of lower cumulative continence rate (p = 0.0457). Conclusions: MRIL measured during surgery was not associated with postoperative continence recovery after RP. We observed that an excessively long membranous urethra compared to the urethral length on preoperative MRI is predictive of poorer postoperative continence recovery. However, small sample size and potential confounding surgical factors limit the significance of this study.